( 1 ) , ( 2 , 3 , 4 ) , ( 5 , 6 , 7 , 8 , 9 ) , ( 1 0 , 1 1 , 1 2 , 1 3 , 1 4 , 1 5 , 1 6 ) , …
Find the sum of the numbers present in the 23rd bracket.
Clarification: 1 is in first bracket, likewise 2, 3, 4 are in the second bracket and so on.
Try more problems here .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice observation!
We note that the number of terms or numbers in k th bracket is given by n k = 2 k − 1 . For k = 2 3 , n 2 3 = 2 ⋅ 2 3 − 1 = 4 5 .
We also note that the last term of k th bracket is the sum of numbers of terms from first to k th brackets inclusively. That is, l k = 2 n k ( n k + 1 ) . For k = 2 3 , l 2 3 = 2 n 2 3 ( n 2 3 + 1 ) = 2 4 5 ( 4 5 + 1 ) = 5 2 9 . The last term of 22nd bracket is l 2 2 = 2 4 3 ( 4 3 + 1 ) = 4 8 4 , therefore, the first term of the 23rd bracket is l 2 2 + 1 = 4 8 5 . Therefore, the sum of the numbers in the 23rd bracket is:
S 2 3 = 2 n 2 3 ( a 2 3 + l 2 3 ) = 2 4 5 ( 4 8 5 + 5 2 9 ) = 2 2 8 1 5
Notice that, the numbers in each bracket are in Arithmetic Progression .
Also, notice that, first term, last term and number of terms in n t h bracket is n 2 − 2 n + 2 , n 2 and 2 n − 1 respectively.
Using the fact that the sum of terms in an Arithmetic Progression that consists of n terms such that first term is a and last term is b is given by 2 n ⋅ ( a + b ) , we can write :-
S n = ( 2 n − 1 ) ⋅ ( n 2 − n + 1 ) .
,where S n denotes the sum of numbers present in the n t h bracket.
On putting n = 2 3 , S 2 3 comes to be equal to 2 2 8 1 5 .
Problem Loading...
Note Loading...
Set Loading...
The pattern goes on as follows:
The sum of the number in the first bracket: 1
The sum of the numbers in the second bracket: 9
The sum of the numbers in the third bracket: 3 5
The sum of the numbers in the fourth bracket: 9 1
...........
So the pattern is 1 , 9 , 3 5 , 9 1 , … Let n be the number of the bracket.
So the sum of the numbers in any bracket can be calculated as ( n ) 3 + ( n − 1 ) 3 .
eg.The sum of numbers in the 3 r d bracket = 3 3 + 2 3 = 3 5 .
Therefore the sum of the numbers in the 2 3 r d bracket = 2 3 3 + 2 2 3 = 2 2 8 1 5 .